Latissimus dorsi flap – the main force in breast reconstruction for breast tumor in Chinese population - Zheng, Shuyue; Hao, Shuang; Chen, Jiajian; Zhang, Yingying; Yang, Benlong; Huang, Xiaoyan; Liu, Guangyu; Shao, Zhimin; Wu, Jiong (Frontiers in Oncology, 2023)
Background: The latissimus dorsi flap (LDF) is the most commonly used autologous flap for breast reconstruction (BR) in China. We conducted this study to explore the current status of BR using LDF with/without implants. Methods: This study was a single-center retrospective study that included breast tumor patients who underwent LDF breast reconstruction at Fudan University Shanghai Cancer Center (FUSCC) between 2000 and 2021. Results: We analyzed 4918 patients who underwent postmastectomy BR, including 1730 patients (35.2%) with autologous flaps. LDF was used for BR in 1093 (22.2%) patients, and an abdominal flap was used in 637 (13.0%) patients. The proportion of LDFs used in autologous BR patients decreased each year and dropped to approximately 65.0% after 2013 due to the increased use of abdominal flaps. Among these patients, 609 underwent extended LDF (ELDF) BR, 455 underwent LDF BR with implants, and 30 received a LDF as a salvage flap due to previous flap or implant failure. Patients who underwent ELDF reconstruction were older and had a higher BMI than those who received a LDF with implants. There was no significant difference in the mean postoperative hospital stay, neoadjuvant chemotherapy rates, or adjuvant radiotherapy rates between the two groups. Major complications requiring surgical intervention occurred in 25 patients (2.29%). There was no significant difference in the incidence of major complications between the two groups (P=0.542). Conclusions: LDF breast reconstruction is a well-developed and safe procedure. The duration of postoperative hospitalization nor the incidence of major complications was affected by implant use.